Bronchoscopic findings in children with non-cystic fibrosis chronic suppurative lung disease. Issue 11 (1st November 2002) - Chang, A B; Boyce, N C; Masters, I B; Torzillo, P J; Masel, J P
Abstract : Background: Published data on the frequency and types of flexible bronchoscopic airway appearances in children with non-cystic fibrosis bronchiectasis and chronic suppurative lung disease are unavailable. The aims of this study were to describe airway appearances and frequency of airway abnormalities and to relate these airway abnormalities to chest high resolution computed tomography (cHRCT) findings in a cohort of children with non-cystic fibrosis chronic suppurative lung disease (CSLD). Methods: Indigenous children with non-cystic fibrosis CSLD (>4 months moist and/or productive cough) were prospectively identified and collected over a 2.5 year period at two paediatric centres. Their medical charts and bronchoscopic notes were retrospectively reviewed. Results: In all but one child the aetiology of the bronchiectasis was presumed to be following a respiratory infection. Thirty three of the 65 children with CSLD underwent bronchoscopy and five major types of airway findings were identified (mucosal abnormality/inflammation only, bronchomalacia, obliterative-like lesion, malacia/obliterative-like combination, and no macroscopic abnormality). The obliterative-like lesion, previously undescribed, was present in 16.7% of bronchiectatic lobes. Structural airway lesions (bronchomalacia and/or obliterative-like lesion) were present in 39.7% of children. These lesions, when present, corresponded to the site of abnormality on the cHRCT scan. Conclusions: Structural airway abnormality is commonly found in children with post-infectious bronchiectasis and a new bronchoscopic finding has been described. Airway abnormalities, when present, related to the same lobe abnormality on the cHRCT scan. How these airway abnormalities relate to aetiology, management strategy, and prognosis is unknown.